Portraying English Teachers’ Obstacles in Applying 2013 Curriculum for High School Level - Karolis Anaktototy (Makassar State University, 2021)
Abstract. Curriculum is an essential part in education. Every change occurs in the national curriculum requires readiness of teachers to cater the demand of the new curriculum. This research was aimed at portraying the obstacles encountered by high school English teachers in Ambon city in applying the new Indonesian national curriculum known as Curriculum 2013. Survey method was used as research method. Questionnaire was used as the instrument in collecting data needed in this study. Data collected were analyzed using descriptive statistics. There were 20 English teaachers from 10 high schools as participants. From the analysis results, this study confirms that most teachers understand the Curriculum 2013 . However, some teachers are still facing some difficulties. These difficulties include the use of learning technology, the availability of learning resources, and the allocation of learning time. The results of this study can be used as a consideration in developing training program for the Curriculum 2013 implementation to be more effective and follow the needs of teachers. Keywords: Curriculum 2013 , teaching English, teachers’ perception